A bibliography of Canadian Inuit periodicals: a case study in Omeka.net migration. Issue 2 (26th November 2020) - Rankin, Sharon
Abstract : Purpose: This paper aims to describe the migration steps taken by a humanities librarian to create a new searchable website for an indigenous bibliography on the Omeka.net cloud-based service. Design/methodology/approach: Using CSV files and Excel, the bibliography entries were moved from the old website to the new one, carefully mapping the descriptive information into Qualified Dublin Core metadata elements. Findings: After resolving diacritic and other data normalization issues, the new site was created in Omeka.net with ease. The plugins available for Omeka.net allowed the editor to geolocate the site of publications. Using TimelineJS, the editor was able to create several timelines and link them to the new CanInuit website as an exhibition. Originality/value: This is a unique application of the Omeka.net cloud-based service.